TINGKAT PENGETAHUAN DAN MOTIVASI IBU DALAM MEMBERIKAN BABY SPA PADA BAYI - wulandari, idah ayu; Parwati, Ni Wayan Manik (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Introduction: Baby Spa is one of the therapies that can increase the growth and development of the baby. Motivation for its implementation there is a need for mother's motivation. Motivation that is influenced by knowledge is very necessary for mothers to give baby spa for their babies. Objective: To analyze the relationship between knowledge and mother's motivation to giving baby SPA for their 3-12 months infants. Method: This study was an analytical study with a cross sectional approach using saturated samples. The population of this study was all mothers who had examined themselves at BPM Idah Ayu Wulandari who had babies aged 3-12 months, they were 29 peoples. The data collection tool was a questionnaire. Data was analyzed by using Rank Spearman. Results: The majority of respondents have high levels of knowledge and high levels of baby spa motivation. There is a significant relationship between knowledge and motivation to giving baby spa (p value 0.002, r = 0.559). Conclusion: It was expected for Midwives Practive Independently (BPM) to active provide counseling/information about baby spa and mothers want to give a baby spa for their babies.